1 Importance of classification and reassessment in patients with pah-chd: the norpap database. (2nd February 2018) - Bingham, R; Abraham, D; Baral, R; Edge, H; Head, C; Lewis, C; Freeman, LJ
Abstract : Purpose: Patients with Pulmonary Arterial Hypertension associated with Congenital Heart Disease (PAH-CHD) are subdivided into 4 categories: Eisenmenger Syndrome, PAH with systemic–to–pulmonary shunts, PAH with coincidental defects, PAH after defect correction. The purpose of this study was to classify all patients on our database with PAH-CHD. The poster contains 3 case studies of patients with Trisomy 21 who were reassessed given this classification, and subsequent learning points are emphasised. Methods: The NORPAP database was created in 1993 and contains 2854 patients. Patients with PAH-CHD were extracted from the NORPAP database and the above classification system applied. Results: 98/2854 (3.4%) of patients had PAH-CHD. Trisomy 21 in 40 patients. Underlying condition shown in figure 1, classification of PAH-CHD in figure 2. 55/98 (56%) are on targeted therapy. Pre-treatment 6 min walk mean 288.5 m, post-treatment mean 320.6 m. Paired two sample t-test analysis reveals a significant difference in 6 min walk test (t-stat 2.02, p 0.01). Conclusion: Targeted therapy in PAH-CHD improves quality of life, delays time to deterioration and may have a mortality benefit. Our limited data supports the evidence that targeted therapy improves objective exercise tolerance. Adult follow up surveillance clinics must be alert to deterioration of functional class in Category 1; Trisomy 21 patients that have been labelled as PAH, but may have normal pulmonary pressure at right heart catheterisation; high index of suspicion with new symptoms in repaired CHD who develop PAH (Category 4).